Les usages et les valeurs des biographies de sportifs de haut niveau comme matériaux d’enquête - Hugo Juskowiak; Williams Nuytens (Communication)
What is the added value of second-hand knowledge when combined with source material ? To answer this question, the authors offer a methodological exercise whereby they graft data from 21 commercial biographies of renowned European soccer players onto source material taken from 90 personal interviews with professional trainers and young recruits and, to a lesser extent, from classic literature in the fields of sociology and sports history.